Hubungan Antara Literasi Digital Dengan Kreativitas Siswa Kelas V Madrasah Ibtidaiyah At Taqwa Kebonagung Dan Madrasah Ibtidaiyah Islamiyah Geluran Sidoarjo Jawa Timur - Miftachul Urbania; Hanik Yuni Alfiyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The inability of students to understand digital literacy which has an impact on unsatisfactory learning outcomes. This study aims to find out how the digital literacy skills of Madrasah Ibtidaiyah students in Sidoarjo, East Java, how the creativity of students in Madrasah Ibtidaiyah in Sidoarjo, East Java, and to find out how digital literacy relates to the creativity of Madrasah Ibtidaiyah students in Sidoarjo, East Java. The method used in this study is a type of quantitative research correlation approach. The independent variable in this study is digital literacy and the variabe tied to this study is the creativity of Madrasah Ibtidaiyah students in Sidoarjo, East Java. The population in this study is Madrasah Ibtidaiyah schools in Sidoarjo, East Java, while the sample was taken by cluster random sampling method and it can be concluded that the sample is grade V students in every two Madrasah Ibtidaiyyah with a total of 199 in the 2022/2023 school year. Data collection in this study through literature studies and field studies using observation, creativity tests, questionnaires, and documentation. Based on the results of the data analysis conducted, it is known that the Digital Literacy of Madrasah Ibtidaiyah in Sidoarjo, East Java is in the very good category, this can be seen from the total score of 88%. The creativity of Madrasah Ibtidaiyah students in Sidoarjo, East Java is in the very good category, this can be seen from the total score of 89%. For the results of calculating the relationship between the two variables using the SPSS 26.0 For Windows application of 0.688 which contains the understanding that the relationship of the independent variable (Digital Literacy) to the dependent variable (Student Creativity) is 68%.